Flutter cookbook : over 100 proven techniques and solutions for app development with Flutter 2.2 and Dart - Alessandria, Simone; Kayfitz, Brian (Packt Publishing Ltd., 2021)
Discover how to build, scale, and debug native iOS and Android applications from a single codebase using the Dart programming language – a hands-on approach Key Features Work through practical recipes for building mobile applications with Flutter Quickly build and iterate on your user interface (UI) with hot reload Fix bugs and prevent them from reappearing using Flutter's developer tools and test suites Book Description“Anyone interested in developing Flutter applications for Android or iOS should have a copy of this book on their desk.” – Amazon 5* Review Lauded as the ‘Flutter bible’ for new and experienced mobile app developers, this recipe-based guide will teach you the best practices for robust app development, as well as how to solve cross-platform development issues. From setting up and customizing your development environment to error handling and debugging, The Flutter Cookbook covers the how-tos as well as the principles behind them. As you progress, the recipes in this book will get you up to speed with the main tasks involved in app development, such as user interface and user experience (UI/UX) design, API design, and creating animations. Later chapters will focus on routing, retrieving data from web services, and persisting data locally. A dedicated section also covers Firebase and its machine learning capabilities. The last chapter is specifically designed to help you create apps for the web and desktop (Windows, Mac, and Linux). Throughout the book, you’ll also find recipes that cover the most important features needed to build a cross-platform application, along with insights into running a single codebase on different platforms. By the end of this Flutter book, you’ll be writing and delivering fully functional apps with confidence. What you will learn Use Dart programming to customize your Flutter applications Discover how to develop and think like a Dart programmer Leverage Firebase Machine Learning capabilities to create intelligent apps Create reusable architecture that can be applied to any type of app Use web services and persist data locally Debug and solve problems before users can see them Use asynchronous programming with Future and Stream Manage the app state with Streams and the BLoC pattern Who this book is for If you’re familiar with the basic concepts of programming and have your eyes set on developing mobile apps using Dart, then this book is for you. As a beginner, you’ll benefit from the clear and concise step-by-step recipes, while a more experienced programmer will learn best practices and find useful tips. You’ll get the most out of this book if you have experience coding in either JavaScript, Swift, Kotlin, Java, Objective-C, or C#.